2020
DOI: 10.1001/jamanetworkopen.2020.3560
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Visual Impairment and Decline in Cognitive Function in a Multiethnic Asian Population

Abstract: IMPORTANCE With the rapidly aging population, the burden of visual impairment (VI) and cognitive decline is expected to increase. Previous cross-sectional studies suggest an association between these 2 health outcomes. However, few longitudinal reports have examined this association, and to our knowledge, no studies have been performed in Asian populations. Further investigation on this association may help to better identify individuals at risk of cognitive decline. OBJECTIVE To examine the longitudinal assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 57 publications
4
34
3
1
Order By: Relevance
“…As noted, social isolation has been proposed as a potential mediator of the association between decreased sensory and cognitive functions (Livingston et al, 2020; Lim et al, 2020; Wahl & Heyl, 2003; Whitson et al, 2018). Vision and hearing are basic forms of interchange between individuals and their environment.…”
Section: Background and Objectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…As noted, social isolation has been proposed as a potential mediator of the association between decreased sensory and cognitive functions (Livingston et al, 2020; Lim et al, 2020; Wahl & Heyl, 2003; Whitson et al, 2018). Vision and hearing are basic forms of interchange between individuals and their environment.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Sensory impairments may also increase the cognitive load required for sensory processing, which may lead to poor cognitive outcomes (Pigeon et al, 2019) or result in direct alteration of brain structure, including both regional and whole-brain atrophy, due to decreased afferent sensory input (Hultsch et al, 1999; Lin et al, 2014; McEwen, 2000; Peelle et al, 2011,Whitson, 2018). Conversely, preserving sensory function may be protective of cognitive function and brain structure in both vision (Lim et al, 2020; Tamura et al, 2004; Xu et al, 2014) and hearing (Dawes et al, 2015).…”
Section: Background and Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Vision impairment (VI), which affects over 1 billion people globally [7], may be one such modifiable risk factor since up to 80% of VI and blindness is avoidable or treatable, often with low-cost interventions like cataract surgery and eyeglasses [8]. In various settings and populations, prior studies have demonstrated that VI is associated with cognitive decline and dementia [9][10][11][12][13][14]. However, several important gaps remain in understanding the nature of this association.…”
Section: Introductionmentioning
confidence: 99%